Identification of intracerebral hemorrhage in the early‐phase of MM1+2C‐type sporadic Creutzfeldt–Jakob disease: A case report. Issue 4 (4th May 2020) - Akagi, Akio; Iwasaki, Yasushi; Yamamoto, Akihiro; Matsuura, Hiroshi; Ikeda, Toshimasa; Mimuro, Maya; Riku, Yuichi; Miyahara, Hiroaki; Kitamoto, Tetsuyuki; Yoshida, Mari
Abstract : We report a case of early‐phase sporadic Creutzfeldt–Jakob disease (sCJD) complicated by intracerebral hemorrhage (ICH), classified as MM1 + 2C‐type based on autopsy. A 61‐year‐old Japanese man presented to our hospital with speaking difficulties including repeated usage of the same words. He was hospitalized on the seventh day after symptom onset, and diffusion‐weighted images on magnetic resonance imaging showed hyperintense regions in the frontal cortex and caudate nucleus. On the 11th day after symptom onset, head computed tomography revealed ICH in the right occipital and parietal lobes. Routine laboratory evaluations and angiography revealed no cause of ICH. Myoclonus of the extremities and drowsiness were observed on the 15th day after symptom onset. He reached the state of akinetic mutism approximately two months after symptom onset. The cerebrospinal fluid test revealed positive real‐time quaking‐induced conversion and 14‐3‐3 protein. Electroencephalography revealed periodic sharp wave complexes. A clinical diagnosis of probable Creutzfeldt–Jakob disease was made according to the diagnostic criteria. After a relapse of pneumonia, he passed away on the 103rd day after symptom onset. Postmortem examination revealed ICH in the right posterior cingulate gyrus. No pathological change that might have caused ICH was obtained. Although the effect of sCJD on the onset of ICH is undeniable, the cause of ICH was unknown. Prion protein immunohistochemistry revealed the following results: (1) weak synaptic‐type deposits in the tissue rarefacted by ICH; (2) synaptic‐type deposits in the cerebral cortex, which showed fine vacuoles; and (3) perivacuolar‐type deposits in the inferior temporal gyrus and lingual gyrus, which showed frequent large confluent vacuoles. Although it could be considered MM1‐type sCJD clinically, this case was neuropathologically diagnosed as having MM1 + 2C‐type sCJD. It was shown that ICH may occur in early‐phase sCJD. To improve sCJD prognosis, treatment of complications and careful follow up are important. Furthermore, pathological diagnosis is indispensable for sCJD type diagnosis.